MANAGEMENT OF ISLAMIC MSME DIGITALIZATION IN KERINCI REGENCY: CHALLENGES, ADAPTATION STRATEGIES, AND IMPLICATIONS FOR LOCAL COMPETITIVENESS - Pardinal; Lastari, Pratiwi Puji; Novia; Mayasari, Mike (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2026)
Digital transformation has become an urgent need for Micro, Small, and Medium Enterprises (MSMEs) in the Industry 4.0 era, particularly in facing technological disruption and shifting consumer behavior. This study aims to construct the concept of MSME Digitalization Management in Kerinci Regency by examining challenges, adaptation strategies, and their implications for local competitiveness. The research method employed is a qualitative descriptive approach with data collection techniques including in-depth interviews, observation, and documentary studies. The results indicate that the implementation of digitalization still faces significant hurdles regarding digital literacy, limited infrastructure, and social resistance to change. Nevertheless, several MSMEs have successfully adapted through digital innovations such as online marketing, the use of e-commerce platforms, and collaboration among local business actors. The implementation of digitalization management is proven to have a positive impact on increasing operational efficiency, expanding market reach, and ensuring business sustainability. This study recommends strengthening the digital ecosystem through synergy between local governments, educational institutions, and business actors to achieve inclusive and sustainable digitalization. Thus, the findings of this study offer a theoretical contribution to the development of locally based digital management models as well as practical implications for enhancing regional economic competitiveness.